2022
DOI: 10.3390/diagnostics12123173
|View full text |Cite
|
Sign up to set email alerts
|

Role of Contrast-Enhanced Ultrasound in the Follow-Up after Endovascular Abdominal Aortic Aneurysm Repair

Abstract: Background: The aim of this study was to assess whether contrast-enhanced ultrasound (CEUS) shows a false negative rate close to zero and therefore is suitable as the main non-invasive follow-up strategy for long-term monitoring after endovascular aortic repair (EVAR). Methods: We included all consecutive patients who underwent CEUS as follow-up after EVAR at our center between January 2017 and December 2021.The follow-up protocol consisted of Duplex ultrasound (DUS) with CEUS at 1, 3, 6 months postoperatively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…In a comparative retrospective study, CEUS reported a sensitivity of 97.4% in endoleak detection using CT angiography (CTA) as a reference standard [ 37 ]. Compared with CTA, the contrast medium used in CEUS is not nephrotoxic and had a low risk for patients [ 38 ]. However, a major drawback of CEUS is operator dependence, which reduces the availability of CEUS [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a comparative retrospective study, CEUS reported a sensitivity of 97.4% in endoleak detection using CT angiography (CTA) as a reference standard [ 37 ]. Compared with CTA, the contrast medium used in CEUS is not nephrotoxic and had a low risk for patients [ 38 ]. However, a major drawback of CEUS is operator dependence, which reduces the availability of CEUS [ 39 ].…”
Section: Discussionmentioning
confidence: 99%